Identifying the prevalence of clinically actionable drug‐gene interactions in a health system biorepository to guide pharmacogenetics implementation services. Issue 2 (12th December 2022) - Pasternak, Amy L.; Ward, Kristen; Irwin, Madison; Okerberg, Carl; Hayes, David; Fritsche, Lars; Zoellner, Sebastian; Virzi, Jessica; Choe, Hae Mi; Ellingrod, Vicki
Abstract: Understanding patterns of drug‐gene interactions (DGIs) is important for advancing the clinical implementation of pharmacogenetics (PGx) into routine practice. Prior studies have estimated the prevalence of DGIs, but few have confirmed DGIs in patients with known genotypes and prescriptions, nor have they evaluated clinician characteristics associated with DGI‐prescribing. This retrospective chart review assessed prevalence of DGI, defined as a medication prescription in a patient with a PGx phenotype that has a clinical practice guideline recommendation to adjust therapy or monitor drug response, for patients enrolled in a research genetic biorepository linked to electronic health records (EHRs). The prevalence of prescriptions for medications with pharmacogenetic (PGx) guidelines, proportion of prescriptions with DGI, location of DGI prescription, and clinical service of the prescriber were evaluated descriptively. Seventy‐five percent (57, 058/75, 337) of patients had a prescription for a medication with a PGx guideline. Up to 60% ( n  = 26, 067/43, 647) of patients had at least one DGI when considering recommendations to adjust or monitor therapy based on genotype. The majority (61%) of DGIs occurred in outpatient prescriptions. Proton pump inhibitors were the most common DGI medication for 11 of 12 clinical services. Almost 25% of patients ( n  = 10, 706/43, 647) had more than one unique DGI, and, among this group of patients, 61% had a DGI with more than one gene. These findings can inform future clinical implementation by identifying key stakeholders for initial DGI prescriptions, helping to inform workflows. The high prevalence of multigene interactions identified also support the use of panel PGx testing as an implementation strategy.